Are matrix metalloproteinases the missing link? - F Mannello (Invertebrate Survival Journal, 2005)
It is more and more evident that the matrix metalloproteinase (MMP) system is not a characteristic feature of vertebrate animals only, as it can also be found in many invertebrate organisms. This endopeptidase family has been widely studied since its first member was described 40 years ago during metamorphosis in tadpole tails. Many researches have been carried out in mammals in order to elucidate and analyze the several and important roles these endopeptidases play, both in physiological pathways and in pathological processes. The evolving researches of these multifaceted enzymes enter the very interesting and fascinating world of the invertebrates, where these enzymes seem to be in the front line during important biological events. MMP-like enzymes and their inhibitors have been found in insects, crustaceans, mussels, sea urchins and also in organisms as simple as hydra. In these species MMPs partake in several fundamental processes, such as extracellular matrix (ECM) remodelling, embryonic development, cell growth and differentiation and also in defense mechanisms thus highlightening their intriguing and unexpected functional importance in invertebrate life too.